Modeling decisions for artificial intelligence : 13th International Conference, MDAI 2016, Sant Julià de Lòria, Andorra, September 19-21, 2016. Proceedings /: 13th International Conference, MDAI 2016, Sant Julià de Lòria, Andorra, September 19-21, 2016. Proceedings. (2016) - Unknown
No abstract available